2014
DOI: 10.1002/stc.1710
|View full text |Cite
|
Sign up to set email alerts
|

Optimum tuning of Tuned Mass Dampers for frame structures under earthquake excitation

Abstract: Summary Tuned Mass Damper (TMD) devices are one of the oldest vibration control means and are widely used in different engineering contexts. Despite the bulk of literature on various TMD‐related issues, the effectiveness of TMDs in reducing the earthquake response of civil engineering structures is still debated. This paper deals with the optimum tuning of the free parameters of a passive TMD applied to sample frame structures subjected to selected seismic excitations. A tuning procedure consisting of a numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 33 publications
3
65
0
Order By: Relevance
“…e optimization procedure here proposed resembles tuning procedures for TMD-based control strategies [10,20,27,44], wherein some parameters are the free design variables sought in the optimization problem, while other parameters are supposed known. e TMDI is characterized by four parameters in the most general case, namely, μ t , β t , ω t , and ζ t .…”
Section: Optimal Design Of the Tmdi And Tuningmentioning
confidence: 99%
“…e optimization procedure here proposed resembles tuning procedures for TMD-based control strategies [10,20,27,44], wherein some parameters are the free design variables sought in the optimization problem, while other parameters are supposed known. e TMDI is characterized by four parameters in the most general case, namely, μ t , β t , ω t , and ζ t .…”
Section: Optimal Design Of the Tmdi And Tuningmentioning
confidence: 99%
“…The identification of structural dynamic properties at seismic input pursues various goals, as response prediction, condition assessment, Structural Control and Health Monitoring, or damage identification. () Nearly all of the available attempts towards these ends pertain to the realm of Experimental Modal Analysis (EMA),() since they need the knowledge or measurement of the input ground motion. However, in most practical cases, the true foundation input motion turns out to be unavailable or unreliable (e.g., not recorded, recorded with low signal‐to‐noise ratio, or affected by soil‐structure interaction (SSI) effects()).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown to be very efficient in reducing the response to a narrow band of loading frequencies in such systems as well. Indeed, many works extended the optimal design problem of TMDs to MDOF systems (see, e.g., these studies). Some works, however, found that a single TMD was less efficient in reducing the responses of MDOFs to a broadband input such as earthquakes .…”
Section: Introductionmentioning
confidence: 99%